COMPLEMENTARY AND ALTERNATIVE MEDICINE (CAM) IN THE FIRST STAGE OF LABOR PAIN: A LITERATURE REVIEW - Dwi Apriani; Ulfah Musdalifah; Tecky Afifah Santy Amartha (Proceedings of the International Conference on Applied Science and Health, 2019)
Background: Excessive pain in labor leads to the side effects on the maternal and neonatal health. Many strategies for labor pain management have been studied, including complementary therapies, yet the comparison of the effectiveness among them needs to be explored more. This study aims to analyze the effectiveness of complementary therapies to reduce pain in the first stage of labor.Methods: This was a literature review using electronic databases from Google Scholar, PubMed, Science Direct, EBSCOhost and text books. The keywords of searching literature were ‘complementary therapy’, ‘pain’, and ‘first stage labor’. All articles reviewed in this study were written in English and Indonesian language with the published year 2010 until 2018.Results: In total, there were 44 out of 232 publications included in this study. Complementary therapies that can be used to reduce first-stage labor pain were aromatherapy, acupressure, and hypnotherapy. Using lavender aromatherapy, pressing the point of L14, SP6, BL32 as well as the use of hypnobirthing showed significant influence in reducing the pain at the first stage of labor among pregnant women.Conclusion: Acupressure is more effective in reducing the pain at the first stage of labor than other alternative techniques. In order to effectively manage the pain at the first stage of labor, a combination of complementary therapies and pharmacological treatment is needed.